Implementasi Motivasi, Kompensasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Pada Masa Covid-19 - Arjuna, Syukron; Melia, Yona (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the implementation of motivation, compensation and work environment on job satisfaction during Covid-19. Data collection in this study was conducted through a survey approach with a type of quantitative descriptive research by distributing questionnaires to 31 respondents, while the population used in this study are employees of Nuansa Resort Hotel Rantauprapat. Data collection techniques were carried out by interviews, questionnaires and documentation studies. Data analysis tools used in this study using SPSS (Statistical Product Software Solution). Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significant Test (t test), simultaneous significant test (F test), and coefficient of determination test (R2). The results of this study show that partially (t test) it is known that partially the implementation of motivation has a positive and significant effect on job satisfaction during Covid-19 in Nuansa Resort Hotel Rantauprapat with a count value of 2.788 > ttable 1.705 and a significance level of 0.010 < 0.05. Partially, compensation has a positive and significant effect on job satisfaction during Covid-19 at Nuansa Resort Hotel Rantauprapat with a count value of 2.168 > ttable 1.705 and a significance level of 0.039< 0.05. Partially, the work environment had a positive and significant effect on job satisfaction during the Covid-19 period at Nuansa Resort Hotel Rantauprapat with a count value of 2.153 > ttable 1.705 and a significance level of 0.040 < 0.05. In simultaneous testing (F test), it is known that the implementation of motivation, compensation, and work environment has a positive effect and job satisfaction during Covid-19 at Nuansa Resort Hotel Rantauprapat with the results showing that the F value is 6.543 > Ftable 2.96 and the significance level is 0.002 < 0.05. Through testing the coefficient of determination (Adjusted R Square) that job satisfaction can be explained by the implementation of motivation, compensation, and work environment by 34.7%. While the remaining 65.3% influenced by other variables that are not examined in this study.